Answer:
4th bubble
Explanation:
First FOIL: f(x) = x² + 3x - 4. Then convert from Standard Form [y = Ax² + Bx + C] to Vertex Form [y = A(X - H)² + K], where (h, k) is the vertex and -h gives the OPPOSITE terms of what they really are. So, you do this by completing the square [½B]²:
- 2¼ = [½(3)]² [then figure out figure out how much you need to get to -4 (k)]
- 2¼ - 6¼ = -4
- Your vertex formula is y = (x + 1½)² - 6¼.
Remember, -h gives the OPPOSITE terms of what they really are, so your vertex is (-1½, -6¼).
If you are ever in need of assistance, do not hesitate to let me know by subscribing to my channel [USERNAME: MATHEMATICS WIZARD], and as always, I am joyous to assist anyone at any time.